The healing (Kentucky brothers, 2,, 2011)
Widower Samuel Fisher is persuaded by his brother to move with his four young children from Lancaster County, Pennsylvania, to Kentucky where he begins working with a contractor on a bed-and-breakfast owned by Englisher Bonnie Taylor, while Esther Beiler helps care for his children, and it is not long before Esther develops a crush on Samuel and a true affection for his children, but she fears Bonnie may have already claimed his heart.

The healing jar (Prayer jars, 3,, 2019)
After Lenore's fiancée calls off their engagement, she resigns herself to being permanently single, but while working in her grandmother's garden she digs up an old jar that may help her find healing. An Amish schoolteacher in her late twenties still living at home with her parents and grandparents, Lenore Lapp thought love had passed her by. When she meets Jesse Smucker, a widower with a baby daughter, she falls in love with them both and accepts Jesse's proposal of marriage. But Jesse is looking for a marriage of convenience, and breaks off their engagement when he realizes Lenore wants love and children. While working in her grandmother's garden, Lenore digs up an old jar with a note inside Will solving long-buried family secrets help heal her broken heart? -- adapted from back cover

The forgiving jar (Prayer jars, 2,, 2019)
"Sara Murray had never met her mother's parents and was surprised to learn after her death that they were Amish living in Pennsylvania. When she is finally able to make the trip to meet them, she is shocked to learn someone else has been living with them and pretending to be Sara. Sara can't understand how quickly her grandparents are willing to forgive the imposter. Secrets and deceit seem to follow Sara, and she is so tired of it. Though soon she meets Brad Fuller who is visiting her grandparents for Christmas. She likes him a lot, but even he seems to pull away from her, not being totally honest. Struggling, Sara finds an old canning jar hidden in the barn that is full of encouraging prayers. Can Sara find a way to forgive the past and move on to building new relationships?"--

Woman of courage (Oasis Audio, Shiloh Run Press, 2018)
"A Woman of Courage Makes an Epic Journey Take a three-thousand mile journey with Amanda Pearson as she leaves the disgrace of a broken engagement and joins the work at a Quaker mission in the western wilds. The trip is fraught with danger, and Amanda is near death before reaching her destination. Among those she meets are an Indian woman who becomes her first convert and a half-Indian trapper who seems to be her biggest critic. But love follows her into the wilderness and will determine the course of her future. You are sure to enjoy this historical romance adventure from New York Times bestselling author Wanda E. Brunstetter. Included is the newly-written sequel, Woman of Hope , with Little Fawn's story. Raised as an orphan by a loving white couple, Little Fawn always felt something was missing from her life. She longs to take the news of Jesus to the Nez Perce Indians, but despite being a missionary herself, Little Fawn's mother forbids it. Will White Wolf, her intended, support Little Fawn's decision when she abruptly follows the tribe's migration onto the Plains?" -- ONIX annotation.